The National Standardized Test Policy for English Subject: Students’ Perception - Amirul Mukminin; Putri Ayu Lestary; Yuliana Afifah; Fathiah Rahmadani; Robi Hendra (Journal of Education and Learning (EduLearn), 2017)
The present study was part of a larger study concerned with examining whether students perceived the use of the national standardized test policy was taking the teaching and learning English at schools in the right direction. A total of 267 completed questionnaires received from year 1, 2, and 3 students enrolled at a public university English education program, Indonesia and answered a questionnaire addressing test preparation activities, controversial testing practices, and the use and accuracy of the national standardized test. This study shed light on our understanding of how participants perceived the national standardized test policy had changed the process of teaching and learning English in the classroom.